SECONDARY PHARMACOLOGICAL PREVENTION OF CARDIOVASCULAR DISEASES: OUR ABILITY IN CLINICAL PRACTICE - E. V. Filippov; S. S. Yakushin (Столичная издательская компания, 2015)
The most pressing issues of the secondary drug prevention of the most common cardiovascular diseases are focused. These are arterial hypertension, stable ischemic heart disease, chronic heart failure.